2018
DOI: 10.18805/ijar.b-853
|View full text |Cite
|
Sign up to set email alerts
|

Baicalein ameliorates cadmium-induced hepatic and renal oxidative damage in rats

Abstract: Cadmium (Cd)-induced oxidative damage of liver and kidney and the ameliorative impact of baicalein against hepatotoxicity and nephrotoxicity of rats was studied. Male SD rats were handled with either intraperitoneal cadmium (CdCl2, 2mg/kg) and/or oral baicalein (100 mg/kg) for 4 weeks. The results demonstrated that Cd increased the level of GPT, GOT, BUN in serum and the contents of MDA, GSH, decreased the activities of SOD, CAT, GSH-Px in tissues versus control. Conversely, administration of baicalein restore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…As shown in Table 2, the body weight of Cd-induced rats was significantly reduced compared with that of rats in the control group. These results are consistent with those of a previous study (Wang et al 2019). The weight loss of rats may be due to the damage in the intestinal mucosa and the disorder of glucocorticoid system caused by Cd.…”
Section: Effect Of Nar On Caspase-9 and -3 Mrna Expressionsupporting
confidence: 93%
“…As shown in Table 2, the body weight of Cd-induced rats was significantly reduced compared with that of rats in the control group. These results are consistent with those of a previous study (Wang et al 2019). The weight loss of rats may be due to the damage in the intestinal mucosa and the disorder of glucocorticoid system caused by Cd.…”
Section: Effect Of Nar On Caspase-9 and -3 Mrna Expressionsupporting
confidence: 93%
“…GSH acts as a major endogenous antioxidant with respect to the gut, GPX transforms GSH to its GSSG oxidized type. Oxidative stress will increase the GSSG level along with a corresponding decrease in SOD, GPX, and GSH concentrations [ 49 , 50 ]. Therefore, we believe that dietary inclusion of GOx has been shown to improve blood profile glucose and SOD of lactating sows by enhancing the immune system.…”
Section: Resultsmentioning
confidence: 99%
“…It is difficult for animals and humans to excrete Cd as it can be present in the body for as long as 30 years ( Nordberg, 2009 ). Previous studies have shown that the liver and kidney are the two main target organs of Cd toxicity and that the degree of damage to the liver is far higher than that of the kidney, and cadmium can even cause liver cancer ( Song et al, 2016 ; Liu et al, 2017a ; Wang et al, 2017 ; Wang et al, 2018 ; Gong et al, 2019 ; Wang et al, 2019 ). The amount that Cd stored in the liver is approximately one third of the total amount of the whole body ( Marettova et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%